Triplet NOAH supersequences optimised for small molecule structure characterisation - Claridge, T; Mayzel, M; Kupče, Ē (Wiley, 2019)
A series of NMR supersequences are presented for the time‐efficient structure characterisation of small molecules in the solution state. These triplet sequences provide HMBC, HSQC, and one homonuclear correlation experiment of choice according to the NMR by Ordered Acquisition using 1H detection principle. The experiments are demonstrated to be compatible with non‐uniform sampling schemes and may be acquired and processed under full automation.